2021
DOI: 10.21203/rs.3.rs-254722/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of Salivary Matrix Metalloproteinases- 12 (MMP- 12) Levels Among Patients Presenting With Oral Submucous Fibrosis and Oral Squamous Cell Carcinoma

Abstract: Background:Oral squamous cell carcinoma is a global threat and accounts for approximately 90% of malignant oral lesions. The emergence of oral carcinoma is linked to precancerous lesions which act as precursors of the disease. Matrix metalloproteinases appear to play a significant role in the pathogenesis of both precancerous conditions and oral malignancies due to their participation in the remodelling of the extracellular matrix.Methodology:This is an analytical study conducted at Dow University of Health Sc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A statistically significant rise in MMP-12 expression was observed in OSMF and OSCC groups compared with healthy individuals. 32 Lipid levels in saliva can be an alternative to serum lipid levels in identifying OSMF. A study suggested a strong relationship between salivary and serum lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…A statistically significant rise in MMP-12 expression was observed in OSMF and OSCC groups compared with healthy individuals. 32 Lipid levels in saliva can be an alternative to serum lipid levels in identifying OSMF. A study suggested a strong relationship between salivary and serum lipid levels.…”
Section: Discussionmentioning
confidence: 99%